A BRIEF OVERVIEW OF CRYPTOGRAPHIC TECHNIQUES: ENCRYPTION, DECRYPTION, RSA AND MORE - Chaudhary, Poonam; Kumar, Vishal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Communication plays a crucial role in today’s information age, with the advancement of new technologies, altogether making security a vital consideration. In order to protect the information being transmitted, having a specific mechanism is of utmost importance. This current era of digitization involves the process of converting original data into an unreadable format, known as encryption, and then reverting it back to its original form, called decryption. The study encompassing both encryption and decryption is referred to as cryptography. This paper aims to analyze various types of cryptography, as well as the concepts of encryption and decryption, and provides a brief overview of cryptographic techniques. When discussing information security, several services come to mind, including confidentiality (information privacy), authentication, and integrity (ensuring data has not been altered). This paper offers a comprehensive description of these cryptographic techniques and focuses on the public key cryptography algorithm, RSA.